Mild cognitive impairment and its determinants in urban and rural areas among older adults: A Cross-Sectional Study - Zeinab Rostami; mahmoud Rahmati; Leili Rostamnia; nader salari (Golestan University of Medical Sciences, 2024)
Background: Mild Cognitive Impairment (MCI) is a transitional stage between normal cognitive aging and dementia, often marked by noticeable cognitive decline without significant interference in daily activities. This study aimed to investigate the prevalence and determinants of MCI among older adults in urban and rural areas of Kermanshah City. Methods: A cross-sectional study was conducted involving 506 older adults recruited from urban and rural areas using a cluster random sampling method. The participants completed assessments of cognitive function, social relationships, stress management, and socio-demographic factors. Logistic regression analyses and the Kruskal-Wallis and Mann-Whitney U tests were performed to examine the associations between these factors and MCI using SPSS version 25. Results: The prevalence of MCI was 21.9% overall, with a higher prevalence in rural areas. In both areas, social relationships (urban: p = 0.001; rural: p = 0.04) and age (urban: p = 0.001; rural: p = 0.013) were significantly associated with MCI. In the rural elderly, education (p = 0.02) and economic situation (p = 0.012) were significant predictors, while in urban areas, gender (p = 0.002) and stress management (p = 0.001) were key determinants. Conclusion: This study highlights the importance of considering psychosocial factors, such as social relationships and stress management, in understanding cognitive health among older adults. Targeted interventions are needed to address the higher prevalence of MCI in rural areas. Further research should explore strategies to improve cognitive health in aging rural and urban populations.